Assessments of toxic heavy metals contamination in cosmetic products. Issue 2 (3rd April 2018) - Ababneh, Fuad A.; Al-Momani, Idrees F.
ABSTRACT: We quantified the contents of four toxic metals in cosmetic products that are commercially available in Jordan; 112 cosmetics, representing 10 product types, were tested in triplicate after acid digestion using inductively coupled plasma optical emission spectrometry and a mercury analyzer. Ni was most abundant, detected in 104/112 (92.8%) products (average, 2.32 ppm; and median, 1.47 ppm); 66/112 (59%) contained >1 ppm and 13/112 (11.6%), >5 ppm Ni. Cd was second-most abundant, detected in 86/112 (76.7%) products (mean, 1.71 ppm; range from< detection limit [DL] to 18.07 ppm); 16 products (14.3%) exceeded the 3 ppm suggested limit. Pb was detected in 82/112 (73.2%) products (mean, 7.8 ppm; range, < detection limit to 190.43 ppm); 20/112 (17.8%) contained more than the suggested 10 ppm limit. Hg was least-frequently detected, present in 29/112 (25.9%) and at >3 ppm in 15/112 (13.4%) products. The highest content of Hg was observed in skin lightening creams (mean concentration, 1, 008 ppm). Hg was detected in 20 (62.5%) of the 32 skin lightening creams tested, of which 11/32 (34.4%) contained > 3 ppm Hg. Of the 112 cosmetics tested, 17 (15.1%) products contained Ni, Pb, Cd, and Hg; 19/112 (16.9%) contained Cd, Pb, and Hg –no product exceeded the maximum acceptable limits for all three elements, and 9/112 (8%) products exceed the maximum recommended levels for at least two elements (Hg, Cd, and Pb).